Flexural behavior of Sisal/Castor oil-Based Polyurethane and Sisal/Phenolic Composites - Milanese, Andressa Cecília [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (ABM, ABC, ABPol, 2012)
Natural fibers used as reinforcement of polymeric composites are interesting research subjects in polymer technology. Nowadays, these materials are being considered as a way to reinforce timber structures improvement. Fibers with larger structural applications are glass and carbon fibers, however, the use of natural fibers is an economic alternative and present many advantages such as biodegradability and having its origin from a renewable source. Castor oil, a triglyceride vegetable with hydroxyl groups, was reacted with 4,4' methylene diphenyl diisocyanate (MDI) to produce the polyurethane matrix. The composites were prepared by compress molding at room temperature using woven sisal fiber as a reinforcement, with and without thermal treatment (at 60 ºC for 72 hours) to the fabrics before the composites molding process. The present paper presents the preparation and a flexural caracterization of sisal/polyurethane and sisal/phenolic composites by using the three-point bending. The sisal fibers moisture content influence on the flexural behaviour was also analyzed. Experimental results showed a higher stiffness for the sisal/phenolic composite (11.2 MPa) followed by the sisal/polyurethane (3.7 MPa), respectively.
Keywords: flexural behavior; castor oil-based polyurethane; sisal fiber; polymeric composite